PARTISIPASI MASYARAKAT DALAM PENETAPAN WILAYAH PERTAMBANGAN MINERAL DAN BATUBARA DI INDONESIA - Deni Yusdianto (JURNAL AKTA YUDISIA, 2022)
AbstractMining activities are fundamentally an activity to optimize the utilization of mining natural resources (minerals) found in the earth. Minerals contained in the earth are processed and then used to be beneficial for the community. The mining sector has been recognized as a source of prosperity that contributes to Indonesia's national income. However, the management of mining activities still has serious problems, particularly regarding the lack of community participation in determining mineral and coal mining areas in an effort to achieve the fulfillment of the needs of the people at large to support sustainable national development in order to realize people's welfare and prosperity in a just manner. The lack of community involvement in determining mining areas will greatly impact the problems that arise as a result of the impact of mining management carried out by a mining company. Therefore community participation is very much needed because it can minimize the main problems that often arise in the mining industry, namely economic, social and cultural problems in mining areas. Based on this background, the issues raised in this study are, first, how is the transformation of the regulation of Community Participation in Determining Mineral and Coal Mining Areas in Indonesia, and the second problem is how ideal Reconstruction is regarding community participation in determining mining areas. This research uses a type of normative legal research, with the approach used is the statutory approach, the conceptual approach and the case approach.The results of the research show that essentially, public participation in determining mining areas is very clearly regulated by several normative rules, both through Law Number 3 of 2020 concerning Minerals and Coal as well as by several Constitutional Court Decisions including Constitutional Court Decision No. 32/PUU- VIII/2010. Furthermore, reconstruction also needs to be carried out to provide new space for community participation through the institutionalization of community participation by establishing a village-level Licensing Institution that functions to control and assess social costs resulting from mining activities.Keywords: Public Participation, Community Participation, Mining Area